Correction: 3-Hydroxypropionaldehyde (3-HPA) quantification by HPLC using a synthetic acrolein-free 3-hydroxypropionaldehyde system as analytical standard. Issue 117 (11th November 2015) - Burgé, G.; Flourat, A. L.; Pollet, B.; Spinnler, H. E.; Allais, F.
Abstract : Correction for '3-Hydroxypropionaldehyde (3-HPA) quantification by HPLC using a synthetic acrolein-free 3-hydroxypropionaldehyde system as analytical standard' by G. Burgé et al., RSC Adv., 2015, 5, 92619–92627.